The internationalization of public management reinventing the third world state - McCourt, Willy; Minogue, Martin; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
The internationalization of public management constitutes one of the first attempts to examine the conceptual and practical problems which attend such policy transfers, and to make preliminary judgements about the successes and failures of public management reform in developing countries. The distinguished group of contributors offers instructive insights into the complex reality of the development state.
1. The internationalization of new public management -- 2. Should flawed models of public management be exported? : issues and practices -- 3. Administrative reform in core civil services : application and applicability of the new public management -- 4. New public management and development : the case of public service reform in Tanzania and Uganda -- 5. Local government : management or politics? -- 6. The NPM agenda for service delivery : a suitable model for developing countries? -- 7. Reinventing the third world state : service delivery and the civic realm -- 8. Privatization and regulation in developing countries -- 9. Human resource management and new public management : two sides of a coin that has a low value in developing countries? -- 10. Information systems and public sector reform in the third world -- 11. Moving the public management debate forward : a contingency approach.
Includes bibliographical references and index.
Keywords: Public administration -- Developing countries; Civil service -- Developing countries; Developing countries -- Economic policy; Local government -- Developing countries; Electronic books